Recent Discoveries on the Role of TOR (Target of Rapamycin) Signaling in Translation in Plants. Issue 2 (9th November 2017) - Schepetilnikov, Mikhail; Ryabova, Lyubov A.
Abstract : TOR signaling regulates plant translation via a specific translation initiation mechanism: reinitiation.